KONSELING DENGAN PENDEKATAN RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK MENGATASI KEBIASAAN MEROKOK - Rina Lestari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2018)
Smoking is an act of waste and waste on property. The purpose of this study were to described: 1) smoking habits of students before giving Rational Emotive therapy? ; 2) student smoking habits after giving Rational Emotive therapy ?; and 3) the effectiveness of Rational Emotive counseling therapy in reducing students' smoking habits. This research was used pre test & post test design. The population in this research were all class X students of SMAN 3 Pekanbaru who had smoking habits with totaling 32 students. To determine the sample of this study, the researcher used purposive sampling. Then, through this technique, 5 students were used as the research sample. Besides, the data was analysed by using "t" test. Moreover,  the result of this research showed that: 1) before given emotive rational counseling therapy, students smoking habits are in the high category with an average score of 92.6 and an average percentage of 77.167%; 2) after given emotive rational counseling therapy have decreased,  students smoking habit are in the medium category with an average score of 66.8 and an average percentage of 55.667%; and 3) there is a significant difference between students' smoking habits before and have been given emotive rational counseling therapy that is equal to 4,691. This means that rational emotive counseling therapy is effective to reduce student smoking habits.